The Influence of Employee Engagement and Workload on Employee Performance - Cahyani, Dea (Growth: Journal Management and Business, 2023)
Employee performance is very important in the process of achieving organizational goals, which are structured through vision and mission to produce the best quality and quantity. Human resources currently play a very important role in an organization within a company. Good human resources will certainly have a good influence on the company. The aim of this research is to determine and analyze the influence of employee engagement and workload on employee performance at BPN Bekasi Regency. The population in this study were all employees at BPN Bekasi Regency. Research data was obtained from the results of distributing questionnaires to a total of 154 respondents based on calculations using the Slovin formula from the total population. The analytical method used is a quantitative approach. The collected data was processed with the help of SmartPLS version 3.0 software. The results of this research show that employee engagement and workload have a positive and significant effect on employee performance.